2014
DOI: 10.1523/jneurosci.4050-13.2014
|View full text |Cite
|
Sign up to set email alerts
|

Biphasic Mechanisms of Amphetamine Action at the Dopamine Terminal

Abstract: In light of recent studies suggesting that amphetamine (AMPH) increases electrically evoked dopamine release ([DA]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
61
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(71 citation statements)
references
References 29 publications
(1 reference statement)
8
61
2
Order By: Relevance
“…In contrast, the authors also showed that higher concentrations of only 10 μM amphetamine induced dopamine release via a DATindependent mechanism. These data further support the idea that low doses of amphetamines are insufficient to disrupt vesicular sequestration and act solely as inhibitors of DAT (Siciliano et al, 2014).…”
Section: Dose Dependent Effects Of Amphetamine and Methamphetaminesupporting
confidence: 78%
See 1 more Smart Citation
“…In contrast, the authors also showed that higher concentrations of only 10 μM amphetamine induced dopamine release via a DATindependent mechanism. These data further support the idea that low doses of amphetamines are insufficient to disrupt vesicular sequestration and act solely as inhibitors of DAT (Siciliano et al, 2014).…”
Section: Dose Dependent Effects Of Amphetamine and Methamphetaminesupporting
confidence: 78%
“…However, it has been suggested that high concentrations of amphetamine (N100 μM) would be required to accomplish this effect (Schwartz et al, 2006). More recently Siciliano et al (2014) demonstrated that low concentrations (10 nM) of amphetamine cause DAT-dependent dopamine release. In contrast, the authors also showed that higher concentrations of only 10 μM amphetamine induced dopamine release via a DATindependent mechanism.…”
Section: Dose Dependent Effects Of Amphetamine and Methamphetaminementioning
confidence: 99%
“…Specifically, this potentiation was found with the lower NOC-12 concentrations (300 and 400 lM), after 15, 30, and 45 min (data not shown) of incubation with Amph, but not at the higher ones. DA release induced by Amph has been shown to be DAT dependent at low concentrations, such as 10 or 100 nM, whereas at high concentrations, such as 10 lM, the same used here, it involves vesicular depletion (Siciliano et al 2014). Our results suggest that Amph 10 lM added to NOC-12 at 400 lM may have reached a ceiling effect on DA release.…”
Section: Neurotox Resmentioning
confidence: 50%
“…Statistical analysis was performed by one-way ANOVA followed by Duncan post hoc, P \ 0.05 and, together with the toxic effects of DA and Amph (described bellow) on DA neurons, are decreasing DA (Trabace and Kendrick 2000). It also should be taken into account that Amph-induced DA release is dependent on DAT, especially under low doses of Amph (Siciliano et al 2014) and levels of DAT may influence the effects of DA releasers and vary across brain regions (Calipari et al 2015). Therefore, the present results should be interpreted considering the limitations of experiments made with primary mesencephalic cell culture, which cannot reproduce such regional variation in DAT and the influence of other brain regions on these cells.…”
Section: Neurotox Resmentioning
confidence: 99%
“…Given the role of DAT in removing DA after release, it is plausible that lower levels of DAT in MA vs cocaine addiction may lead to greater amphetamine-induced DA occupancies (recorded with PET) in MA users, ie, an apparent lack of 'blunting'. Indeed, a recent study suggests that in MA users lower DAT levels are associated with increased methylphenidate-induced DA signal (Volkow et al, 2015); heterozygote DAT KO mice (+/ − ), unlike homozygotes (− / − ) (Jones et al, 1998), had increased amphetamine-induced DA response in the striatum compared wth the wild type (+/+) (Ji and Dluzen, 2008); low dose of amphetamine as used in our human neuroimaging studies might depend more on DAT blocking (vs vesicular depletion) to increase extracellular DA (Siciliano et al, 2014).…”
Section: Pet [ 11 C]-(+)-phno Bp Ndmentioning
confidence: 81%